Perception and knowledge of dementia prevention and its associated socio-demographic factors in China: A community-based cross-sectional study - Song, Dan; Yu, Doris; Sun, Qiuhua (Frontiers in Neuroscience, 2022)
Background Although considerable progress has been made on the risk factors of dementia, less is known about the extent of the gaps between the general public’s understanding of dementia prevention and contemporary scientific evidence. This study aimed to determine the beliefs and knowledge of dementia prevention among the Chinese general public and examine the socio-demographic factors of the belief and knowledge of dementia prevention. Methods The study adopted a cross-sectional design. A total of 358 Chinese adults aged over 40 years were recruited from four healthcare centers. We designed questionnaires that include items on the belief of dementia prevention, risk factors for dementia, and health education needs regarding dementia prevention based on previous literature. Descriptive statistics and multivariate regression analyses were conducted. Results Only 32.4% of the respondents agreed that dementia is preventable. Less participants were able to correctly identify cardiovascular risk factors (i.e., obesity, diabetes, dyslipidemia, hypertension, unhealthy diet, smoking, and alcohol) as part of dementia risk factors. Younger age, higher education, and having contact with patients with dementia are associated with stronger belief that dementia is preventable. Older age, higher income, higher education, having memory complaint, and having contact with patients with dementia are associated with a better understanding of dementia risk factors. A total of 88.9% respondents thought that they are not well informed of dementia from public education, and most respondents (65%) prefer receiving dementia-related health advice from primary care providers. Conclusion The present study reveals the great gaps between the Chinese general public’s knowledge of dementia prevention and the latest research evidence. Public health educational programs for all age groups are encouraged to close this knowledge gap. More attention and resources should be paid to individuals with low income and low education level as they have limited access to dementia prevention information. Researchers should work in partnership with primary care providers to help translate evidence into community practice with a special focus on the link between cardiovascular risk factors and dementia.